ANALYSIS OF THE PROBLEM OF LEARNING LOSS ON MATHEMATICS LEARNING DUE TO THE COVID-19 PANDEMIC IN GRADE VI OF ELEMENTARY SCHOOLS - Sukmaningthias, Novika; Putri Salsabila , Nadia (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2025)
After the Covid-19 pandemic, schools have started to carry out face-to-face learning (PTM) normally as before the pandemic. However, the implementation of this PTM still has to apply health protocols so that the Covid-19 pandemic does not return. This study aims to analyze mathematics learning problems after the Covid-19 pandemic in elementary School. The research method used is descriptive qualitative. Data collection techniques in this study in the form of observation and interviews. The results of this study stated that many problems were found in students and teachers during learning mathematics. The findings of the problems that exist in students are (1) lack of motivation to learn in students, (2) learning patterns of students who only study at school, (3) teacher centered learning methods, (4) online learning change system towards offline learning, and (5 ) assignment system to students. While the findings of the problems that exist in the teacher are (1) various student behavior, (2) lack of teacher innovation in the learning process, and (3) differences in the past and present learning systems.